An Analysis of the Ancient Babylonian Calendar System and Its Similarities with the Hijri Calendar - putra, Nur Afdal Purnama; M. Ihtirozun Ni’am (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2024)
The Babylonian calendar became one of the most widely followed calendar systems in the history of world civilisation because the Babylonian science was more developed than other nations of its time. One of the calendar systems that adopted the Babylonian calendar system was the Sippar and Elephantine calendars, all of which were in the Middle East, because of these developments it is possible that some lunar-based calendars in the Middle East have similarities with the Babylonian calendar including the Hijri calendar because Muslims were originally a nation living in Arabia (Middle East),  So in this research will be examine the similarities between the Babylonian calendar and the Hijri calendar in aspects of their calendar systems, such as the beginning of the day, the number of days and the beginning of the month. To find out this, the author uses a descriptive analytical literature research method. This research found five similarities between the two calendar systems, namely in terms of the object observed in the determination, the rule of the number of days, the method of determination, the determination of the government authority, and the same day cycle.